Bone-mimicking injectable gelatine/hydroxyapatite hydrogels - Rogina, Anamarija (Array, 2019)
Bioactive synthetic hydrogels have emerged as promising materials because they can provide molecularly tailored biofunctions and adjustable mechanical properties. To mimic the mineralogical and organic components of the natural bone, hydroxyapatite and a tyramine conjugate of gelatine were combined in this study. The effect of various amounts of in situ synthesized hydroxyapatite in gelatine-tyramine on the morphology and physical properties of injectable hydrogels was investigated. Mineralogical identification confirmed successful precipitation of in situ formed hydroxyapatite. Better distribution of hydroxyapatite crystal agglomerates within modified gelatine was found at 5 % of hydroxyapatite, which could be responsible for increased storage modulus with respect to pure gelatine hydrogel. Prepared composite hydrogels are non-toxic and support the proliferation of Hek293 cells.